Prevalence of Nomophobia Syndrome among University Students with Disabilities - Al-Zoubi, Suhail; Al-Hendawi, Maha; Shebani, Zubaida; Almaawali, Mahmood; Al Omari, Omar; Tashtoush, Rami; Al Zoubi, Samer M.; Al-Mamari, Khawla; El-Zraigat, Ibrahim (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
This study aimed to identify the prevalence of nomophobia syndrome among university students with disabilities (SWDs) at Sultan Qaboos University (SQU), Oman. A convenience sample of 63 SWDs completed an online Arabic version of the Nomophobia Questionnaire (NMP-Q), which assesses four sub-dimensions: not being able to access information, losing connectivity, not being able to communicate, and giving up convenience. Results showed a high prevalence of nomophobia among SWDs on all four sub-dimensions of the NMP-Q, with no significant differences in levels of nomophobia based on gender or disability category. These results highlight the technological challenges faced by SWDs and point to the need for universities to implement psychological, social, and academic support programs. Interventions that cultivate a healthier relationship with technology, such as workshops that include smartphone use strategies and self-assessment tools to identify personal triggers, can help SWDs manage nomophobia. Integrating nomophobia awareness into university curricula and conducting further research on its impact on academic achievement are also recommended.